Analisis Perhitungan Harga Pokok Produksi Dengan Metode Full Costing Untuk Menentukan Harga Jual Pada UMKM Tahu Payah - Sari, Ayu Mustika; Wahab, Wahyul (CIVITAS: Jurnal Studi Manajemen, 2021)
The purpose of this research are (1) to analyze the cost of tofu products calculated by UMKM Tahu Payah, (2) to analyze the cost of goods manufactured using the full costing method for UMKM Tahu Payah, (3) to analyze the difference between the full costing method and the used by UMKM Tahu Payah and their effect on selling prices. The data used in this study are primary data and secondary data. Primary data is taken by conducting direct interviews with owners and employees who work at the UMKM Tahu Payah while secondary data is obtained through related books, other references in accordance with the research title and research results. The results of the data analysis show that the calculation of the cost of goods manufactured by UMKM Tahu Payah is Rp. 367,- while the results of the analysis of the calculation of the cost of goods manufactured used the full costing method are Rp. 423,- so the difference between the full costing method and what the company does is Rp. 56,-. And determined the selling price with full coting method is Rp. 538,-. So the most appropriate method is the full costing method because this method takes into account all costs incurred in the production process